Analisis Penambatan Molekuler Hidrokarbon Seskuiterpen Gaharu Merauke terhadap protein pengikat penisilin pada Acinetobacter baumanii - Prasetya, Yulianto Ade; Luqman, Arif (Poltekkes Kemenkes Bandung, 2026)
Background: Acinetobacter baumannii is a critical nosocomial pathogen associated with a high level of antibiotic resistance, necessitating the exploration of alternative antibacterial candidates from natural sources. Merauke agarwood (Aquilaria malaccensis) essential oil contains various sesquiterpenes; however, molecular-level evidence targeting A. baumannii penicillin-binding proteins (PBPs) remains limited. Objective: This study evaluated the interactions of selected sesquiterpene hydrocarbons, γ-cadinene, kessane, and α-gurjunene, from Merauke agarwood using an in silico approach. Methods: Drug-likeness and ADMET properties were predicted using ADMETLab 3.0, while potential biological activities were assessed with PASS Online. Molecular docking was performed against A. baumannii PBP1a (3UE3) and PBP3 (3UDF) using CB-Dock2, followed by protein–ligand interaction analysis with PLIP. Results: All compounds complied with Lipinski’s rule and showed moderate quantitative estimates of drug-likeness, although high lipophilicity and plasma protein binding were predicted. Docking analysis revealed moderate binding affinities toward both PBPs (−6.2 to −6.7 kcal/mol) and identified conserved hydrophobic interaction regions involving recurrent amino acid residues within each protein. PASS predictions indicated higher probabilities of antibacterial-related activity than inactivity for all ligands Conclusions: These sesquiterpene hydrocarbons from agarwood form stable interactions with A. baumannii PBPs, providing a structural basis for lead scaffolds in structure-based screening. Further studies on oxygenated derivatives, formulation strategies, and experimental validation are recommended. These sesquiterpene hydrocarbons from agarwood form stable interactions with A. baumannii PBPs, providing a structural basis for lead scaffolds in structure-based screening. Further studies on oxygenated derivatives, formulation strategies, and experimental validation are recommended.